Functional characterization of a catalytically promiscuous tryptophan decarboxylase from camptothecin-producing Camptotheca acuminata - Qiao, Chong; Chen, Fei; Liu, Zhan; Huang, Tianfang; Li, Wei; Zhang, Guolin; Luo, Yinggang (Frontiers in Plant Science, 2022)
Tryptophan decarboxylases (TDCs) are a group of pyridoxal 5-phosphate-dependent enzymes involved in the enzymatic conversion of tryptophan into tryptamine, a critical biogenic amine. We herein mined and cloned a TDC-encoding gene, CaTDC3, from camptothecin-producing plant Camptotheca acuminata. The intact CaTDC3 was heterologously overexpressed in Escherichia coli and the recombinant CaTDC3 was purified to homogeneity. HPLC-DAD and HRMS data analyses of the CaTDC3-catalyzed reaction mixture confirmed the catalytically decarboxylative activity of CaTDC3. CaTDC3 shows highly strict stereoselectivity for L-tryptophan. Homology modelling and molecular docking implied CaTDC3’s recognition of L-tryptophan derivatives and analogues. Substrate scope investigations revealed that the appropriate substituent groups on the indole ring, i.e., hydroxylated and halogenated L-tryptophans, could be recognized by CaTDC3 and its decarboxylation reactions generated the corresponding tryptamines. The C-methyl-L-tryptophans were decarboxylated by CaTDC3 efficiently. 1-Thio-L-tryptophan, the NH group of the indole ring replaced by an S atom, could be decarboxylated by CaTDC3. CaTDC3 catalyzed the decarboxylation of 7-aza-L-tryptophan, an N displacement of the C on the aromatic ring, to afford 7-aza-tryptamine. L-Kynurenine, an L-tryptophan degradation product, could be decarboxylated by CaTDC3. The present works uncover a catalytically promiscuous TDC and it is a versatile decarboxylase in synthetic biology for specialized pharmaceutically important substances.